Analyzing the drivers and challenges of feed-in tariff policy in Kenya - Engola, Monica Katungi (Strathmore University, 2019)
Feed-in in Tariffs (FITS) policies are used by many developed and developing countries world over as a mechanism to promote renewable energy development across various technologies including hydro, wind, solar PV, geothermal, biomass and biogas. The tariffs are administratively determined and producers of power from renewable energy sources are guaranteed a right to sell the power generated to an off-taker at a fixed tariff for a set period. The research focused on the Kenyan FIT policy which was introduced in 2008 and revised in 2010 and 2012. The research problem was that if the FIT policy for Kenya remains in place electricity prices will not be competitive, project development will delay, it will not attract investment in some technologies and the country’s energy targets will not be met. The general objective was to analyze the drivers and challenges of the FIT policy in Kenya. The study approach was descriptive and qualitative and relied on secondary data sources and primary data collection from key informant interviews (KIIs). A purposive sample of key informants was used. Qualitative data analysis adopted a thematic analysis approach whereby common themes were identified from the KIIs. Findings from the study reveal that the main drivers for the FIT policy were to promote generation of electricity from renewable sources, attract investment and independent power producers (IPPs) to the sector, reduce transaction and administrative costs and the need for conformity with global standards or commitments. Secondly, findings reveal that the key challenges for the FIT policy relate to the unavailability of technical expertise for policy design and inefficiencies in policy implementation. The findings on alternative mechanisms to promote the generation of electricity from renewable energy sources include net metering, mini-grids and auctions or competitive tendering. FIT policies achieved marginal effects with the lack of impact on the energy industry attributed to ineffective implementation of policies and a general misalignment of interests among stakeholders. The main recommendation from this study is that the FIT policy should be revised to address the challenges associated with it and retained for projects below 10MW and the auction mechanism should be introduced for projects above 10MW. In addition, that net metering and mini-grids should be implemented as alternative options
A Thesis submitted in partial fulfillment of the requirements for the Degree of Masters in Public Policy and Management at Strathmore University
Keywords: Feed-In Tariff Policy